Evaluation of the effects and interactions of initial chlorine and sulphur contents on the release of potassium compounds during biomass combustion. (April 2022) - Cao, Wenhan; Li, Jun; Zhang, Xiaolei
Abstract: In biomass combustion, understanding the effects of chlorine and sulphur release on the release of potassium compounds can help improve and predict the potassium release mechanisms. In this work, a kinetic model is applied to investigate the influences of S and Cl contents on the release of major potassium compounds during combustion. The results indicated that increasing the initial Cl from 3.8 × 10 −5 mol/g biomass to 1.5 × 10 −4 mol/g biomass promotes the maximum release of HCl and KCl by 518% and 273%, respectively, while inhibits the maximum release of KOH and K2 SO4 by 99% and 68%, respectively. Cl in the biomass has directly influence the release of HCl, but indirectly impact the release of KCl; while its existence inhibits the formations of KOH and K2 SO4 by adapting the contents of moisture, KO and KSO3 . Raising the initial S from 2.7 × 10 −5 mol/g biomass to 1.1 × 10 −4 mol/g biomass only significantly affects the release of KOH and K2 SO4 when temperature exceeds 1300 K, the maximum release of K2 SO4 increased by 117%, while the release of KOH shifts from raise to decline. During combustion, S affects the formation and evaporation of K2 SO4 by controlling the formations of intermediate S species. The results showed the model can accurately predict the major potassium compounds in various scenarios, and support the improvement of ash control technologies. Highlights: Raise initial Cl content in biomass significantly promotes the HCl and KCl release. Raise initial Cl content prohibits the release of KOH and K2 SO4 by 99% and 68%. Increase initial S content favours the K2 SO4 release by 117% when temperature exceeds 1300 K. The release of KOH shifts from raise to decline when increasing initial S content.